2001
DOI: 10.1108/eum0000000006484
|View full text |Cite
|
Sign up to set email alerts
|

Linking sponsorship and cause related marketing

Abstract: Sponsorship activities have become a mainstream component of the marketing mix. As such, there are attempts to make these activities more effective by leveraging them using advertising, sales promotions, or in an increasing number of cases, through cause related marketing (CRM). This paper explores the relationship between sponsorship and CRM and identifies the potential opportunities that arise from leveraging sponsorships using CRM. The paper also examines the limitations of CRM as a leveraging strategy, put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 51 publications
6
119
1
1
Order By: Relevance
“…The literature summarized in the exhibits also support Polonsky and Speed's (2001) contention that there has been no boundary spanning research comparing sports sponsoring and cultural sponsoring/cause-related-marketing. Only Quester and Thompson (2001) examined high-level sponsorship effects using more than one real sponsorship (three art festival events), while all other multi-sponsorship research used fictional sponsors representing sports OR cultural/cause-related-marketing contexts, but not both.…”
Section: Previous Researchmentioning
confidence: 63%
See 2 more Smart Citations
“…The literature summarized in the exhibits also support Polonsky and Speed's (2001) contention that there has been no boundary spanning research comparing sports sponsoring and cultural sponsoring/cause-related-marketing. Only Quester and Thompson (2001) examined high-level sponsorship effects using more than one real sponsorship (three art festival events), while all other multi-sponsorship research used fictional sponsors representing sports OR cultural/cause-related-marketing contexts, but not both.…”
Section: Previous Researchmentioning
confidence: 63%
“…Although sponsorship and cause-related-marketing managers frequently have high-level goals for their programs that can include favorable image transfer, attitude enhancement, higher sales, and improved brand equity (Cornwell et al, 2001a;Gwinner & Eaton, 1999;Miyazaki and Morgan, 2001;Polonsky and Speed, 2001), recent surveys of major sponsors have found that large portions spend little or nothing on the measurement of effects and/or use measures that are inappropriate to their communication goals (Thjømøe et al, 2002;Crompton, 2004). …”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…If the goals and strategies of the corporate brand are at odds with those of the social brand's existing co-branded partners then the relationship may be untenable. Further, instead of adding to their reputation for CSR, organizations may find themselves the target of activist groups or consumers angry at what they may perceive to be a cynical marketing tactic (Frankental 2001;Polonsky and Speed 2001).…”
Section: Brand-web Analysismentioning
confidence: 99%
“…(Polonsky & Speed, 2001) The action through which a company, a nonprofit organization, or a similar entity markets an image, a product, a service, or a message for mutual benefit. (Marconi, 2002) A general alliance between businesses and non-profit causes that provide resources and funding to address social issues and business marketing objectives.…”
Section: (Pringle and Thompson 2001)mentioning
confidence: 99%